Characterisation of Synthetic Dye Decolourising Genes and their Enzymes Produced by an Endophytic Fungus Marasmius cladophyllus UMAS MS8 - Ngieng, Ngui Sing (unimas, 2017)
Wide spectrum usage of synthetic dyes particularly by the textile and dyestuff industry has caused serious pollution of rivers and lake due to insufficient treatment of dye containing wastewater by current known wastewater treatment methods. Endophytic fungi were therefore isolated from Melastoma malabathricum (local name: Senduduk) to test for their ability to decolourise synthetic dyes. Screening on agar plate for synthetic dye decolourisation has enabled the identification of an isolate MS8 that is capable of decolourising all the synthetic dye tested. Synthetic dye decolourisation in liquid medium by MS8 further confirmed the ability of the fungus to decolourise both azo and anthraquinone dyes. Comparing the ITS sequence with NCBI GenBank identified the fungus to be Marasmius cladophyllus. Study on the dye decolourising mechanism of M. cladophyllus in liquid medium using RBBR dye showed the fungus degradative capability in decolourising the dye with no dye adsorption on the fungal mycelium. Further ligninolytic enzyme assay revealed that the presence of RBBR dye induced a 70 folds increase in laccase activity by M. cladophyllus. This laccase enzyme after precipitation by ammonium sulphate can also decolourise 90.2% of RBBR dye, 80.0% of Methyl red, 59.1% of Congo red and 56.1% of Orange G in just 24 hours thus indicating that laccase is the dye decolourising enzyme.